[Jandourek, Jan; Halík, Tomáš. Ptal jsem se cest] - Spunar, Pavel (Religio, 1998)
Reviewed works: Jandourek, Jan; Halík, Tomáš. Ptal jsem se cest. 1. vyd. Praha: Portál, 1997. 287 s. Rozhovory. ISBN 80-7178-143-6.